Best resumes for college students and new grads [ jump-start your career! - Kursmark, Louise M. (Jist Works, 2012)
Students and career-center advisors will benefit immeasurably from this outstanding reference. Best Resumes for College Students and New Grads, Third Edition, includes descriptions of skills and attributes that are valuable in the workplace, answers to common questions, expert advice that is relevant in today's hiring market, and features a showcase of high-quality resumes and cover letters prepared by professional resume writers all written fro college students or new graduates. This comprehensive resource is appropriate for diverse college majors, both undergraduate and graduate, as well as for students seeking internships and co-op jobs while still in school. New for this edition: New chapter on using social media and other online resources in job search and career management.